Not your standard deviation - Tan, Adeline Poh Kim (2019)
Not Your Standard Deviation explores issues surrounding non-normative lifestyles in conservative and heteronormative Singapore. Our project was inspired by the increasingly deviant behaviour of our generation - from schoolmates and close friends, to individuals making waves in the public space for sharing their stories. We cast our net and got responses from an array of non-normative communities including transgenders, gender non-conforming individuals, couples in wide age gap relationships, polyamorous triads, and sugar babies. The overarching theme was showcasing these individuals’ journeys to the ‘forbidden side’ and what ‘monsters’ they encounter along the way, allowing the reader to live vicariously through our articles. A large portion of our newsmakers came from mutual friends. We found that it was easier to gain access to such sensitive topics this way. We also spoke with experts for an impartial viewpoint and wider perspective.